Separation of Silver by Ion-Exchange Resin and Its Determination by Electrothermal Atomic Absorption Spectrometry - Chamsaz, M.; Riazi, M.M. (Asian Journal of Chemistry, 2011)
In this investigation a novel and extremely sensitive method for separation and determination of silver in aqueous samples by ion-exchange resin combined with electrothermal atomic absorption spectrometry is described. In this method 100 mL of Ag+ in pH 4.5 at room temperature is separated with Chelex-100 ion-exchange resin. After separation, the resin is washed by a solution inclusive of 0.5 M HNO3 concurrent with 0.4 % (w/v) thiourea and 20 μL of washing solution is directly transferred into a graphite tube together with coinjection of 20 μL Cu2+ 0.2 % (w/v) as matrix modifier. In this investigation the type of washing solution, concentration of washing solution, pH of sample solution, concentration of thiourea, rate of sample solution and ionic strength were optimized. Using 100 mL sample solution, an enrichment factor of 10 was obtained. The detection limit was calculated to be 0.2 ng mL-1 based on 3Sb and relative standard deviation for five replicate analysis of 1.00 ng mL-1Ag+ was 5.1 %. The calibration curve was linear in the range of 0.2 ng mL-1 to 3.0 ng mL-1 with a sensitivity of 20.0 pg mL-1. This method was used for determination of silver in tap water, waste water, sea water and soil sample.